Analisis Jaringan Sosial Pasar Sunday Morning (Sunmor) di Universitas Gadjah Mada Yogyakarta - Mona Erythrea Nur Islami (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2016)
Sunday Morning Market is a weekly market that is open on Sundays morning in the Gadjah Mada University area. It is a place for informal traders to sell their goods. The analysis shows that there are some patterns of social networks between traders, suppliers and buyers in the Sunday Morning market. The formation of social networks among traders is a horizontal network, based onkinship ar friendship. They have the same resources and obligations to be exchanged. The social relationship itself will be manifested in help each other. The social networks formed through kinship has an important role to overcome social pressures, poverty, unemployment and limited access in getting economic resources. It is common in the informal trading sector, traditional management is applied based on friendship, kinship or origin. The formation of social networks between traders and suppliers is such a vertical social network, by which the socio-economic status is not worth, as well the exchange of obligations and resources. The relation between them is the patron-client relationship. Whereas social networks between sellers and buyers is based on the network ofinterest, social networks between sellers and buyers are based on the network of interest in each other.